The Conception of Drug Using and its Importance for the Prevention - Nazelskis, Eugenijus (Acta Paedagogica Vilnensia, 2002)
In the article the conception of drug using in scientific literature and legislation of Lithuania is analysed. Drug using is showed as a complicated social phenomenon. It is substantiated that the content of the term „ drug using" and its application is not set in and concept presented in National legislation is narrow and one - sided. In the article shortcoming and insufficiency of widely used conceptions are revealed and substantiated. It is stated that the narrowness of the conception can become a serious obstacle in overcoming drug using in the society. In the context of the conception the process of becoming a drug user is presented. To author’s mind, drug using is a necessity in drug arising because of drug materials and causing a user different health problems and at the same time doing harm to an individual and the society. Drug using can be understood as a mental disease, mental disorder, dependence, result of bad treatment, and course of culture, education or self – education, world outlook, and abnormal psychology. It happens so, because in one case drug using is described by caused of the phenomenon, in another case - according to the effect caused by drugs, and in the other cases - in accordance to the results. The conception of drug using presented in the law of Drug Care of Republic of Lithuania is too narrow and one – sided, requiring more specification. In further research of the causes of drug using spreading it is necessary to clear out why a part of society, including young people, voluntary to choose the opposite to healthy way of life – drug using.